Intimin Facilitates Colonization by Escherichia coli O157:H7 in Adult Ruminants - Cornick, Nancy A. (American Society for Microbiology, 2002)
We compared the magnitude and duration of fecal shedding of wild-type Escherichia coli O157:H7 to that of an isogenic intimin mutant in young adult cattle and sheep. In both ruminant species, wild-type E. coli O157:H7 was shed in greater numbers and for a longer duration than was the intimin mutant.